2019
DOI: 10.1109/access.2019.2922635
|View full text |Cite
|
Sign up to set email alerts
|

$\beta$ Algorithm: A New Probabilistic Process Learning Approach for Big Data in Healthcare

Abstract: In this paper, a new process learning framework that is based on probabilistic learning and predicate logic is proposed. The input of this framework is a set of log files, and the output is a probabilistic predicate-based workflow that describes the process. This paper targets a methodology of learning processes given data and the learning algorithm finds out the logical operators that bind the events described in data and model it using predicate logic. While building the process, the probability of every eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Each type focuses on different research topics. The applications in the research field originated from business [9]- [11], focusing on health [3], [12]- [15], information and communication [16], industry [17], education and other fields.…”
Section: Related Work a Process Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Each type focuses on different research topics. The applications in the research field originated from business [9]- [11], focusing on health [3], [12]- [15], information and communication [16], industry [17], education and other fields.…”
Section: Related Work a Process Miningmentioning
confidence: 99%
“…Using machine learning techniques and considering various types of events, Borkowski et al [11] demonstrated how to perform fault prediction in business processes, and evaluated the scenarios using two commercial datasets, showing that the proposed method is able to predict faults with high accuracy. Zayoud et al [12] proposed a new procedural learning framework based on probabilistic learning and predicate logic, and applied it to medical big data, which can be used to predict the frequency and correlation of medical events. To identify opportunities in the process, Martin [13] conducted a thorough process analysis that could be based on real process execution data captured by health information systems and made recommendations to improve the usability and understandability of medical process mining.…”
Section: Related Work a Process Miningmentioning
confidence: 99%
“…Study toward mining-based implementation has been carried out by Sun et al [13] which deals with the knowledge discovery process associated with eth chronic disease over heterogeneous network. Zayood et al [14] have presented a probabilistic learning approach towards medical big data where the technique deals with a unique learning process. The technique makes use of the log files in order to offer inference towards the mined data right from the workflow.…”
Section: Related Workmentioning
confidence: 99%
“…With selecting one of the object types as a case notion, classic logs and models are flattened and can only provide a specific view on the process, leading to convergence and divergence problems. Besides, they typically consider process instances in isolation (ignoring interactions among them) and are more focused on the behavioral perspective of processes [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…e ′ ≺ e if and only if e ′ ⪯ e and e ′ ̸ = e 5. For a sequence σ, e.g., ins, σ i refers to the i-th element of the sequence, |σ| denotes the length of the sequence and ∂set (σ) converts the sequence into a set.…”
mentioning
confidence: 99%